Phenolic compounds from the stem bark of Saccopetalum horsfieldii Benn. - Alfinda Novi Kristanti*, .- (Scholars Research Library, 2015)
Column chromatographic separation of the methanol extract from the Saccopatlumhorsfieldii Benn’sstem bark yielded four phenolic components including three flavonoids, kaempferol-3,4’-dimethylether(1), quercetin-3,7- dimethylether(2), quercetin-3,7,4’-trimethylether(3), and one alkaloid, liriodenine (4). The structures of these compounds were determined based on UV, IR, HRESIMS, 1Dand2DNMR data